Comparison of two testosterone treatments for heat detector cows - M.D. Heekin; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1983)
Testosterone propionate and testosterone enanthate treated cows were equally effective as heat detectors but the testosterone enanthate treatment required at least 9 fewer injections and less time from first injection unit the cow was active as a detector.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Heat detector; Testosterone; Enanthate